Surgery for Pancreatic and Periampullary Cancer Principles and Practice (Springer Singapore, 2018)
This book covers the full range of advanced surgical techniques for pancreatic and periampullary cancers with a focus on major and minor operative techniques and reconstruction methods. Globally respected surgeons share their expertise and personal views in a "how I do it" manner, supplemented by high-quality illustrations. Starting with initial chapters on surgical anatomy, an overview of these cancers, their classification and imaging, subsequent chapters address surgical techniques for resection and reconstruction in detail. The book also included dedicated chapters on complications, preoperative and postoperative management protocols, pathologic reporting, and the impact of nutrition on the outcome. Divided into 28 chapters, it provides an up-to-date, practical guide to the diagnosis and management of pancreatic cancers for both young and experienced HPB and GI surgeons alike.